Keynes the Stock Market Investor: A Quantitative Analysis - Chambers, David; Dimson, Elroy; Foo, Justin (Journal of Financial and Quantitative Analysis, 2015)
Abstract The consensus view of the influential economist John Maynard Keynes is that he was a stellar investor. We provide an extensive quantitative appraisal of his performance over a quarter century and present detailed analysis of his archived trading records. His top-down approach initially generated disappointing returns with no evidence of any market-timing ability. However, from the early 1930s his performance improved as he evolved into a bottom-up stock picker with substantial active risk and pronounced size and value tilts. Our reconstruction of Keynes’s stock trading provides a unique record of realized performance and sheds light on how equity investing developed historically.